Political, socio-cultural and economic organization of the Twa and Teke (Boma) in the plateaux department in the Republic of Congo: case of the Ngo district from 1960 to 2013 - Dominique Oba (Ridwan Institute, 2022)
In Africa as everywhere else, African societies have known several forms of organization that can be found in Central Africa in the Kongo, Loango and Teke kingdoms. This form of organization is also found in the plateau department and more precisely in the region of Ngo where the Bantu and Tswa have lived since time immemorial. Benefiting from several privileges, gradually becoming lord of the land, although occupying space after the Tswa, the Bantu exert a far-reaching influence and domination over the tswa to the point of considering and transforming them as sub-men. The relations between these two peoples are generally to the advantage of the Bantu. In the region of Ngo, the twa and Teke knew a political, socio-cultural and economic organization which was at the base of their civilization. This study tries to show the influence of this multidimensional organization of these two groups which continue to coexist to this day, particularly from 1960 to 2013.